Transformasi Kebijakan dan Upaya Alternatif Pencegahan Kejahatan Narkotika di Sumatera Selatan - Andy Alfatih; Diana Dewi Sartika; Dyah Hapsari Eko Nueraheni; Nabila Tahira (Society, 2024)
Crime is a daily phenomenon that emerges within society. From a structural-functional perspective, crime is considered disturbing and disruptive to the harmonious and stable order of life (social pathology). Drug-related crime is considered a serious crime, even bordering on extraordinary crime, as it has a significant negative impact on the wider community. The research aims to describe the handling of drug-related crimes by the police apparatus in South Sumatra. The research method used is qualitative research to examine incidents and various data variations that emerge in the field, employing a case study approach. The results and discussions show that the South Sumatra Provincial Police have been responsive in addressing drug-related issues in the province, ranging from prevention to rehabilitation, using 4 approaches: 1) Soft Power Coach, 2) Hard Power Coach, 3) Smart Power Coach, and 4) Corporation. The use of drugs can occur due to several factors, namely Poverty Factors, Environmental Factors, Criminal Involvement Factors, and Dependency Factors, highlighting the need for optimal supervision to prevent individuals who have recovered from relapsing into drug consumption. BNN South Sumatra collaborates with the PKK board to create a drug-free village with the aim of monitoring indications of drug use in the village community and forming a rehabilitation task force that is responsible for socializing the community not to use drugs again and stay away from drug use in the community.